Rapamycin suppresses microglial activation and reduces the development of neuropathic pain after spinal cord injury. Issue 1 (22nd June 2016) - Tateda, Satoshi; Kanno, Haruo; Ozawa, Hiroshi; Sekiguchi, Akira; Yahata, Kenichiro; Yamaya, Seiji; Itoi, Eiji
ABSTRACT: Rapamycin is an inhibitor of the mammalian target of rapamycin (mTOR) signaling pathway, plays an important role in multiple cellular functions. Our previous study showed rapamycin treatment in acute phase reduced the neural tissue damage and locomotor impairment after spinal cord injury (SCI). However, there has been no study to investigate the therapeutic effect of rapamycin on neuropathic pain after SCI. In this study, we examined whether rapamycin reduces neuropathic pain following SCI in mice. We used a mouse model of thoracic spinal cord contusion injury, and divided the mice into the rapamycin‐treated and the vehicle‐treated groups. The rapamycin‐treated mice were intraperitoneally injected with rapamycin (1 mg/kg) 4 h after SCI. The rapamycin treatment suppressed phosphorylated‐p70S6K in the injured spinal cord that indicated inhibition of mTOR. The rapamycin treatment significantly improved not only locomotor function, but also mechanical and thermal hypersensitivity in the hindpaws after SCI. In an immunohistochemical analysis, Iba‐1‐stained microglia in the lumbar spinal cord was significantly decreased in the rapamycin‐treated mice. In addition, the activity of p38 MAPK in the lumbar spinal cord was significantly attenuated by rapamycin treatment. Furthermore, phosphorylated‐p38 MAPK‐positive microglia was relatively decreased in the rapamycin‐treated mice. These results indicated rapamycin administration in acute phase to reduce secondary neural tissue damage can contribute to the suppression of the microglial activation in the lumbar spinal cord and attenuate the development of neuropathic pain after SCI. The present study first demonstrated that rapamycin has significant therapeutic potential to reduce the development of neuropathic pain following SCI. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:93–103, 2017.